2014
DOI: 10.3389/fnins.2014.00082
|View full text |Cite
|
Sign up to set email alerts
|

Acute stress affects risk taking but not ambiguity aversion

Abstract: Economic decisions are often made in stressful situations (e.g., at the trading floor), but the effects of stress on economic decision making have not been systematically investigated so far. The present study examines how acute stress influences economic decision making under uncertainty (risk and ambiguity) using financially incentivized lotteries. We varied the domain of decision making as well as the expected value of the risky prospect. Importantly, no feedback was provided to investigate risk taking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 72 publications
5
73
1
1
Order By: Relevance
“…Interestingly, acute stress affects decision-making under risk and different effects of sympathetic compared to endocrine reactivity have been related to this phenomenon (Pabst et al, 2013). Findings of acute stress affecting risk taking are quite robust (for a recent revision of the literature: Buckert et al, 2014) whereas research on possible sex-related differences is still at the beginning but promising (van den Bos et al, 2013;Buckert et al, 2014). Since our study included only nine women, no final conclusion can be drawn and future studies providing a more in-depth view on possible differences between men's and women's psychobiological stress levels in high-stress occupational populations is warranted.…”
Section: Figurementioning
confidence: 94%
“…Interestingly, acute stress affects decision-making under risk and different effects of sympathetic compared to endocrine reactivity have been related to this phenomenon (Pabst et al, 2013). Findings of acute stress affecting risk taking are quite robust (for a recent revision of the literature: Buckert et al, 2014) whereas research on possible sex-related differences is still at the beginning but promising (van den Bos et al, 2013;Buckert et al, 2014). Since our study included only nine women, no final conclusion can be drawn and future studies providing a more in-depth view on possible differences between men's and women's psychobiological stress levels in high-stress occupational populations is warranted.…”
Section: Figurementioning
confidence: 94%
“…Multiple studies have reported risk-taking increases when decisions are framed as potential financial gains [64–66], though longer stress-to-task latencies have recently been shown to be a factor with respect to decisions under risk [i.e., greater risk taking immediately after stress but reduced risk-taking 45 minutes later; 67] Other studies separating decisions under risk by domain (gain/loss trials) are inconsistent. For instance, acute systemic stress applied in that context has led to an exaggerated reflection effect (i.e., decreased risk-taking for gains but increases for losses) interpreted as a stress-related shift towards habit-based DM [68].…”
Section: Stress and Risk-takingmentioning
confidence: 99%
“…To our knowledge, published studies using the standard TSST-G protocol have thus far mostly been conducted with adults from Germany, Switzerland or Norway (Boesch et al, 2014; Buckert et al, 2014, 2012; Häusser et al, 2012; Jacobsen et al, 2014; Klaperski et al, 2014, 2013; Kumsta et al, 2013; Leder et al, 2013; von Dawans et al, 2011, 2012). Two studies conducted in the United States have used modified versions of the task conducted with groups of 2-3 participants (Childs et al, 2006; Hackman et al, 2013).…”
Section: Group-based Stress Protocolsmentioning
confidence: 99%